Essays on Health Care Provider Behavior - Robertson, Justin Christopher (My University, 2014)
Using innovative econometric methods that condition on observed and unobserved characteristics, I estimate patient-specific treatment effects (in particular, Person-Centered Treatment (PeT) effects) for schizophrenia patients taking atypical antipsychotic drugs. Using these treatment effect estimates, I determine how well physicians matched patients to the appropriate drug. By looking at trends in matching over time, I look for evidence of physician learning. Additionally, using patient-specific treatment effects, I look at geographic variation in a number of measures to better understand variation in quality of care. Lastly, I build a theoretical model to study how the threat of waiving copayments affects the optimal insurance contract between the insurer and the patient and payment contract between the insurer and the provider. I find that the threat of waiving copayments may result in reduced patient welfare.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: geographic variation; heterogeneity; incentives; person-centered treatment effects; physicians; Economics; economics